Gender-related differentially expressed genes in pancreatic cancer: possible culprits or accomplices? - Ramezankhani, Roya; Ghavidel, Afshin Abdi; Rashidi, Saadyeh; Rojhannezhad, Mahbubeh; Abolkheir, Hamid Reza; Mirhosseini, Malihe; Taleahmad, Sara; Vosough, Massoud (Frontiers in Genetics, 2022)
Pancreatic cancer (PC) is one of the leading causes of cancer mortality worldwide, while its incidence and mortality rate in several regions is higher in male patients. Although numerous efforts have been made to enhance the clinical outcomes of existing therapeutic regimens, still their efficiency is low and drug resistance usually occurs in many patients. Besides, the exact underlying molecular basis in making PC slightly more prevalent among males have remained unknown. Providing information regarding the possible association between gender and PC tumorigenesis may offer important clues for how certain molecular cross-talks can affect PC initiation and/or progression. In this paper, we used several microarray expression data to identify the common up- and down- regulated genes within one specific gender which were also specified to have binding sites for androgen and/or estrogen receptors. Using functional enrichment analysis among the others, for all the gene sets found in this study, we have shed light on the plausible importance of the androgenic effectors in tumorigenesis, such as the androgen-regulated expression of GLI transcription factor as well as the potential role of testosterone in extracellular matrix (ECM)–cell interaction which is known for their importance in tumorigenesis. Moreover, we demonstrated that the biological process axon guidance was highlighted regarding the up-regulated genes in male patients. Overall, identification of gene candidates as the possible link between gender and PC progression or survival rates may help in developing strategies to reduce the incidence of this cancer.